UTILIZAÇÃO DO RESÍDUO DA INDÚSTRIA DO AÇO NA DEGRADAÇAO DE CORANTES REATIVOS - Moraes, Giuliano (2015)
The problems caused by textile effluents generates a major concern due to high resistance to decay naturally the substances that form the dyes and risks to health caused mainly by a group of wellknown dyes as azo-dyes that studies show they have a carcinogenic potential.Over the years many technologies have been studied to minimize as much as possible and to solve this problem. Between these alternatives there is the Fenton reaction, based on the catalytic decomposition of hydrogen peroxide in an acidic medium (Fe2 + / H2O2), is a process of great potential for the treatment of effluents. The process can be optimized with a UV radiation source 3.0 and pH values. The process efficiency is compromised when trying to work with pH values near neutrality due to the formation of ferric precipitates. To work around this problem heterogeneous degradation, it is presented as a good option because immobilized forms prevent precipitation occurs Fe + 3. The material used is a residue of the production of steel from scrap and pig iron. The material was characterized by FEG scanning electron microscopy and X-ray Diffraction The kinetics of discoloration of the black reactive dye 5 was accompanied by a spectrophotometer, and process efficiency was 97.4% for 30 minutes each test. 18 tests on the same sample material were performed.One of the advantages offered by this material has a low iron leach rate into the medium, on average,this value was 0.7 mg / L.